Electrical tuning of the LC:PDMS channels - Rutkowska, Katarzyna Agnieszka; Woliński, Tomasz R.; Asquini, Rita; Civita, Luca; Martini, Luca; d Alessandro, Antonio (Photonics Letters of Poland, 2017)
In this paper studies on electrical tuning of optical channels formed by the PDMS-based waveguides infiltrated with liquid crystalline material are presented. In particular, preliminary results of numerical simulations demonstrating changes in optical parameters of the waveguide channels when influenced by electric field applied via flat and IPS electrodes are demonstrated in order to fabricate photonic switches based on optical directional couplers. First experimental trials of sputtering the ITO layer on PDMS substrate are also shown. Full Text: PDF References G. Wypych, Handbook of polymers (Elsevier 2016). CrossRef J.C. McDonald, D.C. Duffy, J.R. Anderson, D.T. Chiu, H. Wu, O.J. Schueller, G.M. Whitesides, "Fabrication of microfluidic systems in poly(dimethylsiloxane)", Electrophoresis 21, 27 (2000). CrossRef Y. Fainman, L. Lee, D. Psaltis, C. Yang, Optofluidics: fundamentals, devices, and applications (McGraw-Hill, Inc., 2009). I. Khoo, Liquid crystals: physical properties and nonlinear optical phenomena (John Wiley & Sons, 2007). CrossRef A. d’Alessandro, L. Martini, L. Civita, R. Beccherelli, R. Asquini, "Liquid crystal waveguide technologies for a new generation of low-power photonic integrated circuits", Proc. SPIE 9384, 93840L (2015). CrossRef R. Asquini, L. Martini, A. d’Alessandro, "Fabrication and Characterization of Liquid Crystal Waveguides in PDMS Channels for Optofluidic Applications", Mol. Cryst. Liquid Cryst. 614, 11 (2015). CrossRef B. Bellini, J. F. Larchanché, J. P. Vilcot, D. Decoster, R. Beccherelli, A. d’Alessandro, "Photonic devices based on preferential etching", Applied Optics, 44, (33), (2005). CrossRef L. De Sio, J.G. Cuennet, A.E. Vasdekis, D. Psaltis, "All-optical switching in an optofluidic polydimethylsiloxane: Liquid crystal grating defined by cast-molding", Appl. Phys. Lett. 96, 131112 (2010). CrossRef W. Zheng, L. Yang, M. Lee, "Vertical Alignment of Liquid Crytals on Polydimethylsiloxane Thin Films", Phot. Lett. Poland 3(1), 8 (2011). CrossRef Y. Saad, Iterative methods for sparse linear systems (SIAM, 2003). CrossRef F. Schneider, J. Draheim, R. Kamberger, U. Wallrabe, "Process and material properties of polydimethylsiloxane (PDMS) for Optical MEMS", Sensors Actuat. A: Physical 151, 95 (2009). CrossRef R. Asquini, A. d’Alessandro, "BPM Analysis of an Integrated Optical Switch using Polymeric Optical Waveguides and SSFLC at 1.55 ?m", Mol. Cryst. Liquid Cryst. 375, 243 (2002). CrossRef R. Asquini, L. Civita, L. Martini, A. d’Alessandro, "Design of Optical Directional Couplers Made of Polydimethysiloxane Liquid Crystal Channel Waveguides", Mol. Cryst. Liquid Cryst. 619, 12 (2015). CrossRef